(untitled) (Research, Society and Development, 2022)
Many studies investigating right to health litigation involving medicines mention “high-cost medicines”. However, detailed data on the characteristics of legal claims for these drugs and their share in terms of volume and spending in right to health litigation involving medicines is scarce. This paper presents a protocol for a scoping review that seeks to determine the profile of legal claims for high-cost medicines in Brazil and calculate the volume of purchases and amount spent on these drugs as a share of overall volume and spending related to right to health litigation involving medicines. Structured following the PRISMA-P checklist, this protocol describes the stages of the methodological framework for conducting the review. Guided by the PCC mnemonic (Population, Concept and Context), we searched for articles and other academic research reports published from 2000 to the present date using the MEDLINE, Embase, LILACS, Scopus, and Web of Science databases and the Brazilian Digital Library of Theses and Dissertations, respectively. Study selection will be performed in two stages (reading of titles and abstracts and assessment of the full-text version of the articles) by two independent reviewers. Any disagreements will be resolved by a third reviewer. We will perform a qualitative and quantitative analysis of the results, which will be presented in a descriptive format using figures, tables, and diagrams. The final review report will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analysis for Scoping Reviews (PRISMA-ScR) checklist. This protocol is registered with the Open Science Framework (DOI: 10.17605/OSF.IO/8PXUB).